Effects of several atypical antipsychotics closapine, sertindole or ziprasidone on hepatic antioxidant enzymes: Possible role in drug-induced liver dysfunction. Issue 4 (16th February 2021) - Platanić Arizanović, Lena; Nikolić-Kokić, Aleksandra; Brkljačić, Jelena; Tatalović, Nikola; Miler, Marko; Oreščanin-Dušić, Zorana; Vidonja Uzelac, Teodora; Nikolić, Milan; Milošević, Verica; Blagojević, Duško; Spasić, Snežana; Miljević, Čedo
ABSTRACT: Chronic use of atypical antipsychotics may produce hepatic damage. Atypical antipsychotics, including clozapine, sertindole, and ziprasidone, are extensively metabolized by the liver and this process generates toxic-free radical metabolic intermediates which may contribute to liver damage. The aim of this study was to investigate whether clozapine, sertindole, or ziprasidone affected hepatic antioxidant defense enzymes which consequently led to disturbed redox homeostasis. The expression and activity of antioxidant enzymes superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), catalase (CAT), and glutathione-S-transferases (GST) were measured in rat livers at doses corresponding to human antipsychotic therapy. Clozapine increased activity of SOD types 1 and 2, GR and GST, but reduced CAT activity. Sertindole elevated activities of both SODs. In ziprasidone-treated rats only decreased CAT activity was found. All three antipsychotics produced mild-to-moderate hepatic histopathological changes categorized as regenerative alterations. No apparent signs of immune cell infiltration, microvesicular or macrovesicular fatty change, or hepatocytes in mitosis were observed. In conclusion, a 4-week long daily treatment with clozapine, sertindole, or ziprasidone altered hepatic antioxidant enzyme activities and induced histopathological changes in liver. The most severe alterations were noted in clozapine-treated rats. Data indicate that redox disturbances may contribute to liver dysfunction after long-term atypical antipsychotic drug treatment.